키워드 빈도와 중심성 분석을 활용한 블록체인 기반 사물인터넷 연구 동향 : 미국·영국·한국을 중심으로 - 이택균 ((사)디지털산업정보학회 논문지, 2024)
This study aims to analyze research trends in blockchain-based Internet of Things focusing on the US, UK, and Korea. In Elsevier's Scopus, we collected 2,174 papers about blockchain-based Internet of Things published in from 2018 to 2023. Keyword frequency and centrality analysis were conducted on the abstracts of the collected papers. Through the obtained keyword frequencies, we tried to identify keywords with high frequency of occurrence and through centrality analysis, we tried to identify central research keywords for each country. As a result of the centrality analysis, research on blockchain, smart contracts, Internet of Things, security and personal information protection was conducted as the most central research in each country. The implication for Korea is that cybersecurity, authentication research appears to have been conducted with a lower centrality compared to the United States and the United Kingdom. Thus, it seems that intensive research related to cybersecurity and authentication is needed.
Keywords: Blockchain; Internet of Things; Centrality; Frequency